CHEMICAL ELEMENT COMPOSITION OF THE SNOW COVER IN THE INFLUENCE ZONE OF THE IRKUTSK ALUMINUM PRODUCTION PLANT - Belozertseva I.A. (My University, 2003)
To summarize, stable correlations have been found between chemical elements as regards their distribution trends. Three groups of elements differing in their concentrations in the snow-soil system have been recognized. The first group (F, Al, Na, Mn, Ba) is characterized by high snow levels with more than 50-fold overabundance relative to the background and moderate (fivefold) soil overabundances. The second group includes Ca and Cu. Their overabundance relative to the background in the snow is 25- to 50-fold and in the soil is three- to fivefold. The third group (consisting of Co, Ni, Sr, Mg, Fe, Ti, V, Cr) is characterized by moderate (8- to 25-fold) overabundances in the snow and very low overabundances (less then threefold) in the soil. The correlation between the snow and soil levels of the elements is evidence of their technogenic origin.